Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ctr.13302
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use in the first year after kidney transplant, correlates, and associated outcomes in diabetic transplant recipients: A retrospective analysis of integrated registry and pharmacy claims data

Abstract: While guidelines support metformin as a therapeutic option for diabetic patients with mild-to-moderate renal insufficiency, the frequency and outcomes of metformin use in kidney transplant recipients are not well described. We integrated national U.S. transplant registry data with records from a large pharmaceutical claims clearinghouse (2008-2015). Associations (adjusted hazard ratio, aHR ) of diabetes regimens (with and excluding metformin) in the first year post-transplant with patient and graft survival ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Vest et al 9 reported that the incidence of metformin use in a cohort of kidney transplant recipients within the first year post‐transplant was <5.0%. Within this study, median 1 year eGFR in both arms was >50 mL/min/1.73 m 2 , making metformin a viable option for the treatment of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vest et al 9 reported that the incidence of metformin use in a cohort of kidney transplant recipients within the first year post‐transplant was <5.0%. Within this study, median 1 year eGFR in both arms was >50 mL/min/1.73 m 2 , making metformin a viable option for the treatment of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…With the established risks of malignancy and diabetes after SOT, understanding metformin's role in this population is necessary. A registry analysis of kidney transplant recipients between 2007 and 2013 found that only 4.7% of patients had been prescribed metformin within the first year post‐transplant despite metformin use being associated with a reduction in all‐cause mortality, including malignancy‐related death, as well as all‐cause graft failure 9 . A recent publication reported that use of metformin in heart transplant recipients was associated with a 90% reduction in risk of malignancy in their diabetic population 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, metformin has been linked to rare but fatal lactic acidosis complications, especially in patients with eGFR <30 mL/min per 1.73 m 2 , which has led the US Food and Drug Administration (FDA) to label it as contraindicated for such patients. Since most donors are expected to have eGFR levels >30 mL/min per 1.73 m 2 , use is likely safe and appropriate, but notably, concern for reduced kidney function was not a deterrent to use, in contrast with infrequent use in the transplant population at higher eGFR levels . In the context of obesity, even independent of diabetes, metformin may have benefit for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…At the crossroads of controversy in the implications of obesity in living donor selection, and in recognition of diabetes mellitus as an important cause of ESRD when it occurs in donors, pursuit of better understanding of the implications of pre‐donation obesity for comorbidity such as diabetes is warranted. Pharmacy claims offer a non‐obtrusive measure of prescribed health care that do not rely on patient self‐report and are increasingly used in observational investigations of large populations including transplant and donation‐related epidemiologic studies . To this end, we examined a novel linkage of national US transplant registry data with records from a pharmacy claims warehouse that identifies antidiabetic medication (ADM).…”
Section: Introductionmentioning
confidence: 99%
“…However, in later phases after transplantation, the NODAT agreement in 2003 did not endorse metformin as the first-line anti-diabetic drug because of safety concerns. In later phases after transplantation, sulfonylureas, meglitinides, dipeptidyl peptidase-4 inhibitors, alpha-glycosidase inhibitors, and rarely sodium-glucose co-transporter 2 (SGLT-2) inhibitors have been suggested as potential anti-glycemic agents (5,6). There is a need for further trial studies to verify an association between PTDM and metformin administration in high-risk renal transplant patients and to evaluate the risk-benefit balance using this drug (7).…”
Section: Pharmaceutical Management Of Ptdmmentioning
confidence: 99%